Finite Element Analysis Of An Actuator In MEMS Application - Ce Ku Zanggi, Che Ku Mohd Arif (Universiti Sains Malaysia, 2005)
There have many applications in MEMS can be developed by a PZT actuator such as in data storage system, medical and RF system. This project focuses on high density data storage system which the PZT actuator namely microheater was placed. The main function of this microheater in high density data storage system is to write and read a data. Thermal performance of this microheater can be measured from experimental or finite element analysis. When a voltage or current was applied on microheater a displacement, resonant frequency and temperatures can be determined. So to evaluate a thermal performance of this microheater, a thermal analysis of this microheater has been done by ANSYS simulation. With the simulation, the tip temperature for thermal writing step at the fixed time can be determined and the time period for thermal cooling step closed to the room temperature, 27 0 C can be predicted. The parametric studies have been done to compare the thermal performance of others parameter of the microheater. The first parametric studies; varied cone tip size, which the cone tip is smaller than cone tip size in verification analysis. Decrease in cone tip size causes the highest tip temperature for thermal writing step due to small size of light doped region. The second parametric studies; varied the shape of microheater and microcantilever give the lowest tip temperature for thermal writing step due to size of doped region and cone tip are more than other two analyses. The longest time period for thermal cooling step give a tip temperature near the room temperature. From the graph, thermal time constant can been found. The thermal time constant has desired to identify a thermal behavior of microheater which the smallest time constant, the fastest of microheater write or read a data. The MEMS fabrication and packaging also can be applied when a thermal performance of microheater has been recognized.